Optic Disk Pit with Sudden Central Visual Field Scotoma - Nikol Panou; Demetrios G. Vavvas (Case Reports in Ophthalmological Medicine)
Purpose. To describe a case of optic disk pit (ODP) with sudden central visual field scotoma. Methods. A 49-year-old woman presented, reporting sudden painless central visual field loss 3 months prior to presentation. Neuroophthalmologic, systematic, and laboratory evaluation and full imaging processes were performed. Results. Fundoscopy and color photography demonstrated an optic disk pit inferotemporally. Perimetry identified central visual field horizontal scotoma. OCT revealed absence of serous retinal detachment, but disclosed inner retina thinning corresponding to the area of the visual field loss. Fluorescein angiography demonstrated delay in the cilioretinal arteries and also disclosed a relative delay in the perfusion of an arterial branch off the inferior retinal arcade. Clinical and laboratory evaluations were negative for any related pathology. Conclusion. Sudden central visual field scotoma in patients with ODP may be associated with delayed vascular filling of CRA and retinal arterioles within the optic disc anomaly region.